(untitled) (Research, Society and Development, 2019)
It analyzes the construction from the comparison of the gypsum method with the conventional method of masonry of bricks and issues considerations about dilemmas and possibilities under the same is of paramount importance for the current days in which the respect for this has been diminished category. The main object is to dissect the general concept of the use of plaster and bricks, delimiting the same to the scope of focus in Brazil. The problematization aims to answer which of the two methods would offer more benefits to the society. The General Objective is to make comparisons between the two methods, informing concepts and possibilities in their conditioning. The specific objectives are to present the history and concepts of both methods, inform models and compare how practices would be, that is, construction. In the end it is realized that the plaster is more economical and easier to operate.